A critical study of Feminist Critical Discourse Analysis of changing Gender Pre-defined expectation in Pakistani Movies - Sohail, Sadia; Sanzar, Bakht; Mehboob, Saima (University of Wah Journal of Social Sciences, 2020)
Literature is one of the social phenomena which reflects and portrays the existing social, political, economic, and religious stances of any society. The movie is one of the literary genres which are made not only for the sake of entertainment but to reflect the realities of the present society explicitly or implicitly. For the present research study, two Pakistani movies (Punjab Nae Jaonge, Balochabad) which are the representation of contemporary Eastern society, are selected to get the purposive data. The study aims to analyze the stances and role of Feminist Critical Discourse Analysis in the social practices of the Eastern world in terms of gender. Feminist Critical Discourse Analysis is one of the frameworks of Critical Discourse Analysis which has been developed and promoted by Lazar in 2007 who stressed asymmetrical power relations in gender discourses. Feminist Critical Discourse Analysis targets to analyze, question, and reconstruct the social practices in gender discourses. Purposive data has been analyzed through qualitative research design having the conversational analysis of the dialogues of the selected movies. The present study carries the findings that Feminist Critical Discourse Analysis has a very vital and significant role in changing the social practices of gender in existing Eastern society that women are now occupying good status in a patriarchal society. Gender discriminative discursive practices are getting change due to the successful placement of Feminist Critical Discourse Analysis.